Method for Increasing the Regularity of Isolation of Infectious Ribonucleic Acid from Influenza Virus - Chetverikova, L. K. (1970)
A more effective method of isolating infectious ribonucleic acid (RNA) from influenza virus was evaluated based on the enzymatic disintegration of the viral coat by Pronase, followed by phenol-detergent extraction of the RNA from susceptible and from resistant cells.